Prediksi Perkembangan Permukiman Pada Kawasan Penyangga di Kota Ambon Menggunakan Cellular Automata - Zulkifli Zulkifli; Ananto Yudono; Ihsan Ihsan (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2016)
Halong area is an area consisting of protected, buffer and cultivation areas. It is feared that the development of settlements in the Halong Region will endanger the buffer zone which is useful for protecting the protected areas in Halong. The purpose of this study is to identify the weights of the variables that affect settlement development and predict settlement development in the Halong Region, Ambon City. The analytical method used is causative associative using cellular automata and kappa validation. Based on the analysis, the variables that influence the development of settlements in the Halong Region are distance to the main road, distance to health facilities, distance to worship facilities, distance to education facilities and distance to trade facilities. Furthermore, by using the weights of each variable and data on the number of houses in 2004, 2010 and 2013, we get a prediction of the development of the number of houses and a map of the distribution of new houses each year from 2014 to 2024.